Effective Factors in Solving the Legal Gaps of Blockchain-based Systems in Dealing with Counterfeiting of Drugs عوامل موثر در رفع شکاف های حقوقی سیستم های مبتنی بر بلاک چین در مقابله با جعل دارو - افسانه قنبری; امیر محمودی; بهنام حبیبی درگاه (Majallah-i Huqūqī-i Biyn/al-milalī-i)
Drug counterfeiting causes global health corruption and hinders the achievement of the Millennium Development Goals and the right to the highest attainable level of standards of health, under Article 12 of the International Covenant on Economic, Social and Cultural Rights. In General Comment No. 14 of the Covenant, access to essential medicines is described as a human right. Although blockchain technology provides a safe and transparent method to track drugs along the supply chain to prevent counterfeiting, the results indicate that this technology has some ambiguities in terms of structure and functionality regarding compliance with existing legal regulations, namely, limitations regarding its implementation. A question can be raised in this matter, and that is, what are the effective factors in solving the existing legal gaps in relation to the laws of the digital space and blockchain? It seems that the governance of the blockchain in the decision-making process and regulation of laws are effective in how the blockchain network works.